The Influence of Job Satisfaction, Work Motivation, and Work Environment on Employee Performance at PT. Gelora Mandiri Membangun - Aryo Indro Prasojo; Mentiana Sibarani (Return : Study of Management, Economic and Bussines, 2025)
The purpose of this study is to look at how job happiness, work motivation, and work environment affect employee performance at the PT. Gelora Mandiri Membangun. Job satisfaction comprises addressing employees' emotional needs and expectations while carrying out their duties. Work motivation is classified into inner elements, such as a sense of accomplishment and self-development, and external factors, such as financial incentives and recognition. The work environment encompasses the physical and social circumstances that either help or impede employee productivity. This study employs a quantitative approach using survey methodologies. The sample comprised of 100 purposively selected respondents. Multiple linear regression approaches were used to determine the impact of independent factors (job happiness, work motivation, and work environment) on the dependent variable (employee performance). The research findings indicate that the third independent variable, job happiness, work motivation, and work environment, has a favorable and significant impact on employee performance. Work motivation was determined to be the most important element impacting employee performance. Furthermore, regression research reveals that the combination of these three factors may account for 65% of the variation in employee performance. Thus, enhancing job happiness, motivation, and work environment will have a major impact on staff performance at PT. Gelora Mandiri Membangun. According to the findings of this research, firms should prioritize techniques that raise motivation and job satisfaction, as well as improve the work environment, in order to boost productivity. Continuous staff development and welfare enhancement activities are recommended.